The wild robot protects - Brown, Peter, 1979- (Brown, Peter, 1979-. Wild robot (Series), 2023)
"Life for Roz and the animals on their island is perfect. But when mysterious, dangerous waters surround the island, the animals are forced inland to fight over dwindling resources. Roz calms and organizes the animals, but the poison tide takes a terrible toll on the island. So the wild robot sets out across the ocean, determined to stop the poison tide. During her journey, Roz encounters amazing geological formations and incredible creatures, and she sees the devastation caused by the toxic waters. Can the wild robot save the ocean and her island and everything she loves? This thrilling third installment of the Wild Robot series takes readers on a new adventure through the ocean and to the frigid northern waters where Roz may have to make the ultimate sacrifice" --